Development of molecular genetic technologies in Pavlov University: 20 years history and achievements - S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
21 years have passed since the signing of the order on the establishment of the Department of Molecular Genetic Technologies of the Scientific Research Center (order № 118 was signed by Academic N. A. Yaitsky on June 5, 2001) and 20 years have passed since the beginning of the Department's activities. The leading scientist in the field of molecular medicine, Professor Evgeny Iosifovich Schwartz, not only headed the Department, but also brought there his team — the team of the Laboratory of Human Molecular Genetics of the Petersburg Nuclear Physics Institute named by B. P. Konstantinov of National Research Centre «Kurchatov Institute». The team was the first in the country to use the polymerase chain reaction (PCR) method to diagnose human hereditary diseases, and at that time had experience both in mapping mutational damage in monogenic human diseases and in its research in the field of multifactorial pathology. The department creation marked the beginning of molecular genetic technologies at the University and became the basis for fundamental scientific researches and the development of modern methods of molecular genetics. The review describes the history of Department and its main achievements.